Rigorous Design of FDIR Systems with BIP - Dragomir, Iulia; Bensalem, Saddek (Electronic Communications of the EASST, 2019)
The correct design of autonomous systems is a challenge, due to the uncertainties arising at execution time. A special case of uncertainties are the faults and failures that break the system’s requirements. Dealing with such situations requires to design fault detection, isolation and recovery (FDIR) components. The aim of FDIR components is to detect when a fault has occurred and to apply a recovery strategy that brings the system into a mode where the requirements are satisfied. In this paper we describe an approach based on the Behavior, Interaction, Priority (BIP) tools for the rigorous design of FDIR components. This approach leverages the scalability of statistical model-checking tool BIP-SMC to check for requirement satisfaction, and the code generation feature of the BIP compiler. Moreover, the generated code is executable with the BIP engine(s) and easily integrated with the original system. The approach has been used in the H2020 ESROCOS and ERGO projects for the development of (autonomous) robotics control systems, which have been validated through field trials.